2021
DOI: 10.1371/journal.pone.0252867
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome, risk assessment, and seasonal variation in hospitalized COVID-19 patients—Results from the CORONA Germany study

Abstract: Background After one year of the pandemic and hints of seasonal patterns, temporal variations of in-hospital mortality in COVID-19 are widely unknown. Additionally, heterogeneous data regarding clinical indicators predicting disease severity has been published. However, there is a need for a risk stratification model integrating the effects on disease severity and mortality to support clinical decision-making. Methods We conducted a multicenter, observational, prospective, epidemiological cohort study at 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
2
18
2
1
Order By: Relevance
“…As shown by our study group, in-hospital mortality showed temporal variation during the year 2020 in the "CORONA Germany" cohort, mostly influenced by age [22]. Also, we assume seasonality of COVID-19 to be noteworthy, as discussed before [22]. Interestingly, incidences of clinically manifest cardiovascular events showed two peaks in our study coinciding with the two waves of infection in Germany.…”
Section: Blood Pressuresupporting
confidence: 69%
See 2 more Smart Citations
“…As shown by our study group, in-hospital mortality showed temporal variation during the year 2020 in the "CORONA Germany" cohort, mostly influenced by age [22]. Also, we assume seasonality of COVID-19 to be noteworthy, as discussed before [22]. Interestingly, incidences of clinically manifest cardiovascular events showed two peaks in our study coinciding with the two waves of infection in Germany.…”
Section: Blood Pressuresupporting
confidence: 69%
“…Lastly, it needs to be considered that the time span covered by this study is wide and includes different waves of COVID-19 infections, burdens on the health care system and the learning curve of this new disease. As shown by our study group, in-hospital mortality showed temporal variation during the year 2020 in the "CORONA Germany" cohort, mostly influenced by age [22]. Also, we assume seasonality of COVID-19 to be noteworthy, as discussed before [22].…”
Section: Blood Pressuresupporting
confidence: 56%
See 1 more Smart Citation
“…In Germany, the first wave was smaller and led to fewer hospitalizations than the second, while the peaks in hospitalizations between the waves were more similar in Sweden. Despite this, the highest mortality in both studies was seen in the initial peak of the first wave 26 . Another study examined raw case fatality ratio (CFR) in 53 countries or regions and showed decreased mortality in the second wave in 43 of them, including in Sweden.…”
Section: Discussionmentioning
confidence: 76%
“…However, the recent COVID-19 pandemic resulted in many people with an acute infectious illness being in need for palliative care. Mortality is highest among male patients, people of old age and people with chronic or malignant diseases [ 3 , 4 ]. Most people die because of respiratory failure, myocardial damage or failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%